2021
DOI: 10.3390/su13105395
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mobility on the Spread of COVID-19 in Light of Regional Differences in the European Union

Abstract: The COVID-19 pandemic has spread rapidly all over the world, affecting many countries to varying degrees. In this study, an in-depth analysis of the factors influencing the spread of COVID-19 is offered mainly through big data in the European Union (EU) context. In doing so, the data of the first wave of the pandemic are assessed. Afterward, we evaluate the impacts of the COVID-19 spread in specific countries and regions. Based on the existing literature, mobility is recognized as a significant direct factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Our scan of the literature led us to conclude that including urban mobility in the model would have greatly increased its complexity, so we chose to exclude it and focus on the objective that we had set for ourselves. However, more studies on the subject are appearing every day [72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Our scan of the literature led us to conclude that including urban mobility in the model would have greatly increased its complexity, so we chose to exclude it and focus on the objective that we had set for ourselves. However, more studies on the subject are appearing every day [72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has also affected the whole of Europe, first involving only some European countries, Italy in particular, and gradually spreading to all member states. 3 A study that examines the degree of impact of the epidemic in the first six months (February to July 2020) of the pandemic in nine EU countries based on their characteristics was carried out by Cheshmehzangi et al (2021). They found that the timeliness of relevant policies and the effectiveness of government implementation indirectly limit the spread of the epidemic by reducing population mobility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The last days of December 2019 witnessed the emergence of a global landmark event as the first confirmed case of an infection with a novel coronavirus was reported in Wuhan, a bustling metropolis nestled in Hubei Province at the heart of Central China. This pivotal moment sparked a series of consequential events that would soon engulf the globe in uncertainty (Cheshmehzangi et al, 2021). The Hubei health authorities sprang into action on 8 January 2020, launching an extensive survey to decipher the nature and extent of this mysterious viral outbreak.…”
Section: Introductionmentioning
confidence: 99%